A Phase II, Single‐Arm, Open‐Label, Bayesian Adaptive Efficacy and Safety Study of PBI‐05204 in Patients with Stage IV Metastatic Pancreatic Adenocarcinoma. (2nd July 2020) - Roth, Marc T.; Cardin, Dana Backlund; Borazanci, Erkut Hasan; Steinbach, Margaux; Picozzi, Vincent J.; Rosemury, Alexander; Wadlow, Raymond Couric; Newman, Robert A.; Berlin, Jordan
Abstract: Lessons Learned : This trial evaluating a novel plant extract, PBI‐05204, did not meet its primary endpoint of overall survival but did show signals of efficacy in heavily pretreated mPDA. PBI‐05204 was generally well tolerated, with the most common side effects related to treatment being vomiting (23.7%), nausea (18.4%), decreased appetite (18.4%), and diarrhea (15.8%). Additional trials are needed to explore the role of PBI‐05204 in cancer treatment. Background: Survival for metastatic pancreatic ductal adenocarcinoma (mPDA) is dismal, and novel agents are needed. PBI‐05204 is a modified supercritical carbon dioxide extract of Nerium oleander leaves. Oleandrin, the extract's major cytotoxic component, is a cardiac glycoside that has demonstrated antitumor activity in various tumor cell lines with a mechanism involving inhibition of Akt phosphorylation and through downregulation of mTOR. Methods: A phase II, single‐arm, open‐label study to determine the efficacy of PBI‐05204 in patients with refractory mPDA therapy was conducted. The primary endpoint was overall survival (OS), with the hypothesis that 50% of patients would be alive at 4.5 months. Secondary objectives included safety, progression‐free survival (PFS), and overall response rate. Patients received oral PBI‐05204 daily until progressive disease (PD), unacceptable toxicity, or patient withdrawal. Radiographic response was assessed every two cycles. Results: Forty‐two patients were enrolled, and 38 were analyzed. Ten patients were alive at 4.5 months (26.3%) with a median PFS of 56 days. One objective response (2.6%) was observed for 162 days. Grade ≥ 3 treatment‐emergent adverse events occurred in 63.2% of patients with the most common being fatigue, vomiting, nausea, decreased appetite, and diarrhea. Conclusion: PBI‐05204 did not meet its primary endpoint for OS in this study. Recent preclinical data indicate a role for PBI‐05204 against glioblastoma multiforme when combined with chemotherapy and radiotherapy. A randomized phase II trial is currently being designed.